How do good governance practices affect mining companies? Peru’s case (2024)
The purpose of this research is to find a relationship between compliance with the principles of good Corporate Governance and the performance of the shares of companies in the mining sector that are listed on the Lima Stock Exchange. The considered time period goes from June 2013 to June 2018. Two portfolios called TIR 1 and TIR 2 were assembled according to the number of principles fulfilled to separate the companies with the highest compliance, TIR 1, from the companies with the lowest TIR 2 compliance. The Carhart four-factor method has been applied. The results showed that the TIR 1 portfolio is superior in performance of the shares compared to the TIR 2 portfolio, which we could comment that there is a relationship between compliance with good practices and the returns of these companies in the sector studied.